2010
DOI: 10.1016/j.vetimm.2010.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin-1 production by the canine macrophage cell line DH82: Enhanced production in response to microbial challenge

Abstract: Endothelin-1 (ET-1) is a potent vasoconstrictive peptide which plays an important role in regulating mammalian cardiovascular development and homeostasis. Originally identified as a factor released by vascular endothelial cells, ET-1 is now recognized as a product of numerous cells and tissues with demonstrated involvement in an array of physiological and pathological processes. An area of great interest is the production of ET-1 by mononuclear cells (monocytes and macrophages) and its role in inflammation. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 50 publications
1
4
0
Order By: Relevance
“…Brain endothelial cells, microglia, astrocytes, and neurons are other sources of ET-1 (78,84). We observed endogenous secretion levels comparable to those found in DH82 cells by Divino et al (37), but we did not observe the reported stimulation with LPS. Methodological differences from that study included DH82 passage levels (85), the preparation of LPS (E. coli O111:B4 versus O127:B8), and endpoint after stimulation (48 h versus 24 h or less).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Brain endothelial cells, microglia, astrocytes, and neurons are other sources of ET-1 (78,84). We observed endogenous secretion levels comparable to those found in DH82 cells by Divino et al (37), but we did not observe the reported stimulation with LPS. Methodological differences from that study included DH82 passage levels (85), the preparation of LPS (E. coli O111:B4 versus O127:B8), and endpoint after stimulation (48 h versus 24 h or less).…”
Section: Discussionsupporting
confidence: 77%
“…M. canis significantly reduced DH82 cell expression of ET-1 (Fig. 6), in contrast to the increases typically resulting from exposure to other bacteria (37,(79)(80)(81). Once more, the effect was greatest for brain isolate UFG1.…”
Section: Discussionmentioning
confidence: 86%
“…Previous publications support the notion that activation of macrophages induces ET-1 production and release. Specifically, it was recently reported that the canine macrophage cell line, DH82, constitutively secretes both ET-1 and its biologically inactive precursor big ET-1 and that the production of both peptides is increased after either stimulation with LPS from Gram-negative bacteria or with intact and viable Gram-positive and Gramnegative bacteria (42). The secretion of ET-1 by polymorphonuclear neutrophils, macrophages, and mast cells increases during inflammation (43,44).…”
Section: Discussionmentioning
confidence: 99%
“…ET-1 is a peptide consisting of 21 amino acids and is mainly secreted by endothelial cells [ 28 ]. It has a strong vasoconstrictive effect and plays an important role in maintaining the basal vascular tone and cardiovascular homeostasis [ 29 , 30 ]. Researchers have found a close relationship between ET-1 and intestinal inflammation, which is a chronic inflammatory bowel disease that includes ulcerative colitis and Crohn’s disease [ 31 ].…”
Section: Discussionmentioning
confidence: 99%